Revising the range of Rocky Mountain tailed frog, Ascaphus montanus, in British Columbia, Canada, using environmental DNA methods. Issue 3 (18th March 2020) - Hobbs, Jared; Adams, Ian T.; Round, Jessica M.; Goldberg, Caren S.; Allison, Michael J.; Bergman, Lauren C.; Mirabzadeh, Ali; Allen, Heather; Helbing, Caren C.
Abstract: The Rocky Mountain tailed frog, Ascaphus montanus, is a species at‐risk in Canada. Based upon time‐ and area‐constrained physical search surveys completed between 1996 and 2004, its Canadian distribution was defined as occurring in 19 tributaries and reaches within the Yahk and west side Flathead River Basins of British Columbia. We undertook a five‐year (2014–2018 inclusive) environmental DNA (eDNA) survey to reassess the distribution of Rocky Mountain tailed frog, focusing on tributaries proximal to known extant occurrence records. Seventeen days of field sampling were performed over the five‐year period. Targeted qPCR‐based eDNA approaches proved more effective than conventional physical search methods for detecting tailed frogs due to relatively rapid field collection, low cost of filter materials, elimination of observer bias, and higher detection probabilities compared to conventional time‐constrained survey methods. One hundred and forty sites were examined (138 for eDNA plus two visual only). Thirty‐two of the 138 sites (23%) tested positive for Rocky Mountain tailed frog DNA, including from the four extant populations sampled, whereas visual observations occurred at only seven of the sites (5%) during the survey. During the study, we evaluated two tailed frog tests and the mitigation of false negatives through testing for qPCR inhibition and sample degradation, and we demonstrate their utility in evaluating eDNA data quality. These results expand the extant range of Rocky Mountain tailed frog in the Flathead, Wigwam, and Yahk watersheds and add two new watersheds (Moyie and Tepee) by identifying five newly recorded occupied drainages in Canada: Elder Creek, Upper Wigwam River, Tepee Creek, Gilnockie Creek, and Elmer Creek. These data are important to refine and augment wildlife habitat conservation areas for Rocky Mountain tailed frog. Abstract : Environmental DNA methods were rigorously compared to conventional time‐constrained survey methods to evaluate the distribution of a species at risk—the Rocky Mountain tailed frog—in locations proximal to known extant occurrences in British Columbia, Canada. The study was performed over a five‐year period with 17 days of survey effort at 140 sites. eDNA methods resulted in a 23% detection compared to 5% visual detection and expanded the extant range of tailed frog to five new drainages in Canada.